A Comprehensive Evaluation of Polymer Additives in Modified Bitumen for Enhanced Pavement Performance (Sebha University Conference Proceedings, 2024)
In Libya, as in many other countries, highway pavements primarily consist of bituminous mixtures, where the bituminous binder, despite its low proportion (5-7% by weight), significantly influences pavement performance. Standard bitumen often fails to meet desired performance levels under repeated traffic loads and adverse weather conditions. Over the last 20-30 years, the necessity to enhance pavement durability and minimize economic and environmental losses has led to the modification of bituminous binders with various additives, notably polymers. Successful bitumen modification requires understanding the characteristics of both the bitumen and the polymer used, as well as optimal production conditions for polymer-modified bitumen. This study compares 2 popular types of polymers (SBS & RUBBER) used in Libya. The results showed that the asphalt mixture with SBS & RUBBER  improved  the rutting % and Stabilty compared to the asphalt mixture without  additives .